2019
DOI: 10.1109/jphot.2019.2918047
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Feynman Gate Based on Suspended Graphene Nano-Ribbon Waveguides at THz Wavelengths

Abstract: In this paper, a plasmonic Feynman gate based on suspended graphene nanoribbon waveguides at THz wavelengths is proposed and numerically investigated. The proposed plasmonic Feynman gate is composed of two cascaded microring resonators. The resonant states of microring resonators are flexibly controlled by tuning chemical potentials of graphene in rings, and thus, the logic operation results of Feynman gate can be performed successfully. Compared to the plasmonic Feynman gate based on graphene nano-ribbons dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Suspended 2D materials offer significant potential for a diverse range of applications due to their ultra-thin nature, high strength, high conductivity, and high transparency. One prominent application lies in electronic devices, including FETs [41,60,61], logic gates [62,63], photodetectors [64][65][66][67][68], resonators [69][70][71][72], and sensors [73][74][75][76][77][78]. For instance, Han et al demonstrated that incorporating piezoresistive properties in suspended graphene membranes enhances sensitivity and expands the temperature-sensing range in nanoelectromechanical system (NEMS) temperature sensors [129].…”
Section: Applications Of Suspended 2d Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Suspended 2D materials offer significant potential for a diverse range of applications due to their ultra-thin nature, high strength, high conductivity, and high transparency. One prominent application lies in electronic devices, including FETs [41,60,61], logic gates [62,63], photodetectors [64][65][66][67][68], resonators [69][70][71][72], and sensors [73][74][75][76][77][78]. For instance, Han et al demonstrated that incorporating piezoresistive properties in suspended graphene membranes enhances sensitivity and expands the temperature-sensing range in nanoelectromechanical system (NEMS) temperature sensors [129].…”
Section: Applications Of Suspended 2d Materialsmentioning
confidence: 99%
“…Ongoing investigation into the properties and characteristics of 2D materials is expected to lead to Additionally, suspended 2D materials exhibit great potential within the of logic gates. Wang et al [62] introduced a plasmonic Feynman gate leveraging suspended graphene nano-ribbon waveguides. In comparison to the plasmonic Fermi gate grounded on a substrate, the plasmonic Fermi gate constructed upon a suspended architecture affords superior performance in terms of extinction ratio and crosstalk mitigation, which furnishes valuable insights in the logic circuits.…”
Section: Applications Of Suspended 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, graphene's optical and electrical properties can be easily tuned by bias voltage. Therefore, people can manually control the status of modulator based on graphene switch between on and off [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%